Public good overprovision by a manipulative provider - Gorkem Celik; Dongsoo Shin; Roland Strausz (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2020)
We study contracting between a public good provider and users with private valuations of the good. We show that, once the provider extracts the users' private information, she benefits from manipulating the collective information received from all users when communicating with them. We derive conditions under which such manipulation determines the direction of distortions in public good provision. If the provider is non-manipulative, the public good is always underprovided, whereas overprovision occurs with a manipulative provider. With overprovision, not only high-valuation users, but also low-valuation users may obtain positive rents - users may prefer facing a manipulative provider.
Keywords: D82; D86; H41; 330; Information Manipulation; Public Goods